WR279,396, a third generation aminoglycoside ointment for the treatment of Leishmania major cutaneous leishmaniasis: a phase 2, randomized, double blind, placebo controlled study. - Afif Ben Salah; Pierre A Buffet; Gloria Morizot; Nathalie Ben Massoud; Amor Zâatour; Nissaf Ben Alaya; Nabil Bel Haj Hamida; Zaher El Ahmadi; Matthew T Downs; Philip L Smith; Koussay Dellagi; Max Grögl (Public Library of Science (PLoS), 2009)
Cutaneous leishmaniasis (cl) is a disfiguring disease that confronts clinicians with a quandary: leave patients untreated or engage in a complex or toxic treatment. Topical treatment of CL offers a practical and safe option. Accordingly, the treatment of CL with WR279,396, a formulation of paromomycin and gentamicin in a hydrophilic base, was investigated in a phase 2 clinical study in Tunisia and France.A phase 2, randomized, double blind, vehicle-controlled study was conducted to assess the safety and efficacy of topical WR279,396 when applied twice a day for 20 days as treatment for parasitologically confirmed CL. The study protocol established the primary efficacy end point as complete clinical response (CCR) defined as 50% or greater reduction in the ulceration size of an index lesion by day 50 (D50) followed by complete re-epithelialization by D100, and no relapse through D180.Ninety-two subjects were randomized. Leishmania major was identified in 66 of 68 isolates typed (97%). In the intent-to-treat population, 47 of 50 WR279,396 treated participants (94%) met the definition of CCR, compared with 30 of 42 vehicle-placebo participants (71%) [p = 0.0045]. Erythema occurred in 30% and 24% of participants receiving WR279,396 and placebo, respectively [p = 0.64]. There was no clinical or laboratory evidence of systemic toxicity.Application of WR279,396 for 20 days was found to be safe and effective in treating L. major CL, and offers great potential as a new, simple, easily applicable, and inexpensive topical therapy for this neglected disease.ClinicalTrials.gov NCT00703924.